Plasmid - Gull, Munazza (IntechOpen, 2019)
This book captures in a single volume the wealth of information on the plasmid structure, function, and biology of all organisms that have been examined to date. Plasmids exhibit wide variations in size, modes of replication and transmission, host ranges, and the genes they carry and have provided us with a great understanding of basic life principles at the molecular level. Written by experts in the field, this book is a valuable source of up-to-date information, delivering the latest impacts on studies in the areas of plasmid types, genomes, purification analysis, and expression of recombinant proteins in bacteria. Plasmid utilization in the synthesis of plasmid-based vaccines, plasmids as genetic tools, and their applications in ecology and the evolutionary process are also covered. This book is a single source of valuable information for instructors and students in advanced undergraduate and graduate courses on plasmids. It will also appeal to researchers seeking to find new relationships between biological processes that are linked by plasmids to the environment.